STRATEGIES IN ENGLISH SPEAKING LEARNING BY THE FOURTH SEMESTER STUDENTS OF ENGLISH DEPARTMENT AT SINTUWU MAROSO UNIVERSITY - Meydi Cristiania; Gitit Indra Putra Wacana; Ika Paramitha Lantu (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
The purpose of this research is to find out the learning strategies used by the fourth-semester students of English Language Education Study Program at Sintuwu Maroso University. The design of this research is qualitative research that uses three kinds of data instruments. namely questionnaires, interviews, and documentations. Each of instrument contains questions related to speaking learning strategies. The object is the fourth semester students of English Language Education Study Program in academic year 2021/2022 enrolled in Academic Speaking Class. The result shows that the fourth semester students of English Language Education Study Program used some learning strategies from O’Malley and Chamot (2012). They used four sub-categories from Metacognitive strategies consisting of Self-Management, Self-Evaluation, Organizational Planning, and Directed-Attention. Four sub-categories from Cognitive consisting of Resourcing, Keyword-Method, Deduction, and Repetition. The fourth semester students used all strategies from Socio-Affective strategies that consisting of Questioning for Clarification and Cooperation